2018
DOI: 10.1007/s11548-017-1698-y
|View full text |Cite
|
Sign up to set email alerts
|

Signal attenuation maps for needle enhancement and localization in 2D ultrasound

Abstract: The proposed method could be useful in challenging procedures where needle shaft and tip are inconspicuous. Improved needle localization results compared to previously proposed methods suggest that the proposed method is promising for further clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 17 publications
3
29
0
Order By: Relevance
“…Furthermore, the amplitude of the Doppler responses generated by the excited needle might be reduced when the needle is inserted at high depths due to the damping of the needle vibrations by the surrounding tissue. Despite the depth-dependent degradation in the lateral resolution, many previous studies, such as [ 12 , 14 ], that proposed needle detection methods based on B-mode ultrasound image analysis showed that the needle can be localized in curvilinear ultrasound images with submillimeter accuracies. In fact, the method presented in the current study was also able to obtain accurate needle localization with submillimeter accuracy by combining power Doppler and B-mode ultrasound image analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the amplitude of the Doppler responses generated by the excited needle might be reduced when the needle is inserted at high depths due to the damping of the needle vibrations by the surrounding tissue. Despite the depth-dependent degradation in the lateral resolution, many previous studies, such as [ 12 , 14 ], that proposed needle detection methods based on B-mode ultrasound image analysis showed that the needle can be localized in curvilinear ultrasound images with submillimeter accuracies. In fact, the method presented in the current study was also able to obtain accurate needle localization with submillimeter accuracy by combining power Doppler and B-mode ultrasound image analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the position of the needle tip along the estimated needle axis is determined using image statistical analysis. Mwikirize et al [ 14 ] introduced a method for enhancing the needle visibility and localizing the needle in curvilinear B-mode images. In this method, the visibility of the needle is enhanced by computing signal attenuation maps that model ultrasound attenuation and scattering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a template-based tracking method with the efficient second-order minimization optimization method has been used to track the needle [16]. In recent studies, more and more novel ideas have been used to locate the needle and evaluate its tip to sagittal US images, such as the use of signal attenuation maps [17], convolution neural networks (CNN) [18], and maximum likelihood estimation sample consensus (MLESAC) method [19]. However, a demerit of using sagittal US images is that out-of-plane bending of the needle cannot be detected.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, attenuation of the US signal due to energy loss beyond the US beam incident with the needle, is used to detect the position of the needle [ 8 , 11 ]. However, signal loss due to the presence of other attenuating structures may degrade the accuracy of estimation and must be explicitly handled.…”
Section: Introductionmentioning
confidence: 99%